Economic valuation of the ecosystem services of provision and landscape from the Historical Sanctuary “Bosque de Pómac” - Gamarra Gonzáles, Julissa del Rocío (2019)
The objective of the research was to determine the economic valuation of the ecosystem services of provision and landscape from the Historical Sanctuary “Bosque de Pómac” and to formulate retribution mechanisms, the methodology of the contingent valuation expressed in the availability to pay was used. 8-item surveys were applied to 374 inhabitants from 14 villages in the buffer zone and 1-item surveys were used to 659 regional, national and foreign visitors of the SHBP, both validated with the Cronbach’s Alfa. Filed work was carried out from June 3rd to November 30th, 2017, central tendency measures were later used and the availability to pay. It was concluded that: 1. The inhabitants from the buffer zone of SHBP expressed their willingness to pay on average S /. 20.98 for a quintal of carob dried fruit; S /.7.45 for a quintal of sapote dried fruit, S /. 22.37 for the fallen branches, better known as the “load of wood” and S /. 10.79 for the kilogram of honey. 2. The inhabitants surveyed showed that they are willing to pay on average S /. 3.94, national visitors S/. 10, 96 and foreigners S /. 24, 48; 3. The average willingness to pay for national visitors was S/. 7.95 for visiting the Historical Sanctuary “Bosque de Pomac” and foreigners agreed to pay S/. 30, 86. 4. The retribution mechanisms proposed by the respondents were the direct payment of the value of the service and actions as part of the voluntary park rangers program.